A inserção da Organização Social no Setor Saúde (OSS) no projeto da assistência no Ceará sob a lente da semiótica - Silva, Marcos Antonio Alves da (2016)
The Brazilian SUS is the result of a revolutionary thought in the thinking of social construction in Health, started in a period of great political ferment of struggle for democratization of the country the construction of SUS, two texts are founding:. The Federal Constitution of 1988 and the law 8080/90. Both belong to the legal discursive domain. This reflection revisited the so-called doctrine of SUS, supported on the following grounds: equality, universality, solidarity, integrity and health as a right of all and duty of the Brazilian state, assumptions that support the Brazilian Health System, essences for which there is no support of the semiotic construction point of view, the existence of the SUS, because these are the utterance and precious values forming to the know-how of the State in achieving the health object. the state, in the text, has a social function main protection of owners and the viability of the property. SUS through federal laws nº. 8.080 / 90 and nº 8.142 / 90 organic laws of health and social control, or community participation, respectively, is included significantly towards the social spheres of Arendt and Habermas public policy. For the analysis of Health in this context we opted for the Semiotics approach proposed by Greimas. The main factor that has Semiotics a theory of choice to guide our textual analysis was her interest by the conditions of apprehension of meaning, placing the text and its organizational structures in the center of the investigation. As a method, we chose the descriptive document and qualitative research. The study took place in Ceará territory. Data collection took place between the months of August to December 2015. The study of the universe were all qualified institutions at the federal, state or municipal government as a Social Organization of Health (OSS), managed by non-profit entities, and the population consisted of those who administer hospital health institutions located in 22 health regions of the state through the Management Agreement. The choice by hospitals in the OS universe was justified by the range of types of institutions that can be classified by the government as OSS. Included were: 01 institution type Autonomous Social Service active in National level with its management contract under the Ministry of Health (MS) which runs a hospital in Fortaleza and 01 Public Social Organization that operates in the state of Ceará with contract linked with the Secretariat of Health of Ceará (SES-CE). It can be concluded that the SUS, subject adjuvant, is the creation of the State for the viability of the right to health. It should always be in close relationship conjunction with the statement and subject the objects values, the fundamentals. Any disjunction, either by misuse or relativization, will place the SUS in the semantic field of the opponent, Non-SUS. Official and Semiotically the Cearense State maintains an appearance of being (p), however, gives by state law the possibility of not being (ñe), ie acts in the use of Social Organizations in the health field under lie sign following different project itself, ie, non-SUS, modalizando their action through different objects value of euforizados by SUS. Applying square veridité and semiotics at the same time the two institutions will obtain non-compliance with the fundamentals, SUS-value objects, the lie and the opinion (p+ ñe), ie, semantics and syntactically, Non-SUS. The APS-SARAH and ISGH included in the semantic field of non-SUS, act not in accordance with their objects value through their own values constructing a narrative and generative route of different SUS sense. As for the Regionalization Cearense process, despite being in the semantic SUS field, ISGH figure in the secret veridité level, because in spite of being part of regionalizador process, so have the semiotic attribute of being (e), the institute does not it seems (ñp) or is not inclined to this end. The APS-Sarah network, stands in the semantic field of non-SUS, and in veridité level lie.